Pelatihan Pengendalian Dampak Negatif Smartphone pada Anak melalui Aplikasi Parental Control - Saputro, Indrawan; Nugraha, Febrianta Surya; Widiati, Ina Sholihah; Widiyanti, Sri; Purwidiantoro, Moch Hari (Jurnal Pengabdian Masyarakat Teknologi dan Pendidikan (MANTAP), 2025)
Uncontrolled smartphone usage among children can lead to various negative impacts—psychological, social, and academic. This community service program aimed to empower mothers from the Dasawisma PKK group by providing training and technical assistance in using parental control applications to manage their children's smartphone use. The activities included interactive education, hands-on demonstrations, and group discussions. A total of 25 participants actively engaged in the sessions. The post-activity evaluation revealed that an average of 92.4% of participants agreed or strongly agreed that the training increased their awareness, knowledge, and intention to supervise children's gadget usage more wisely. The highest agreement (94%) was recorded on items related to digital supervision awareness and training benefits. These results indicate that the program effectively enhanced digital parenting capacity. This initiative is expected to serve as a replicable model for strengthening parental roles in digital supervision within the family setting.